2022
DOI: 10.1007/s00221-022-06389-5
|View full text |Cite
|
Sign up to set email alerts
|

Mental rotation of hands and objects in ageing and Parkinson’s disease: differentiating motor imagery and visuospatial ability

Abstract: Motor imagery supports motor learning and performance and has the potential to be a useful strategy for neurorehabilitation. However, motor imagery ability may be impacted by ageing and neurodegeneration, which could limit its therapeutic effectiveness. Motor imagery can be assessed implicitly using a hand laterality task (HLT), whereby laterality judgements are slower for stimuli corresponding to physically more difficult postures, as indicated by a “biomechanical constraint” effect. Performance is also found… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 79 publications
1
15
0
Order By: Relevance
“…Previous studies on motor imagery ability have examined the relationship between Parkinson’s disease [ 32 , 33 ] and multiple sclerosis [ 34 ] and motor imagery ability. Additionally, various reports have shown that the neural networks activated during motor imagery differ depending on the motor imagery ability [ 21 , 22 ], that the excitability of corticospinal tracts during motor imagery correlates with motor imagery ability [ 23 , 24 ], and that motor imagery ability is related to the effectiveness of motor imagery training [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on motor imagery ability have examined the relationship between Parkinson’s disease [ 32 , 33 ] and multiple sclerosis [ 34 ] and motor imagery ability. Additionally, various reports have shown that the neural networks activated during motor imagery differ depending on the motor imagery ability [ 21 , 22 ], that the excitability of corticospinal tracts during motor imagery correlates with motor imagery ability [ 23 , 24 ], and that motor imagery ability is related to the effectiveness of motor imagery training [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the context of mentally rotating hand positions, PD patients have been found to show asymmetries in their proficiency with clockwise or counterclockwise rotations (Helmich et al, 2007). Scant attention has been paid to whether such biases exist in tests of WM in PD patients (though see (Bek et al, 2022). Here, we were able to monitor, quantify and account for the variety of ways in which these errors could impinge on our performance metrics and ascertain whether there were group differences.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the context of mentally rotating hand positions, PD patients have been found to show asymmetries in their proficiency with clockwise or counter-clockwise rotations (Helmich et al, 2007). Scant attention has been paid to whether such biases exist in tests of working memory in PD patients (though see (Bek et al, 2022).Here, we were able to monitor, quantify and account for the variety of ways in which these errors could impinge on our performance metrics and ascertain whether there were group differences. Although ostensibly the analogue Corsi-like task contains the most opportunities for impaired motor control to affect performance, there was no evidence for systematic biases in patients responded in the horizontal or vertical plane.…”
Section: Response Biases May Influence Recall Errormentioning
confidence: 99%
“…However, these alterations in MI appear to parallel alterations in motor capabilities and so may be reflective of motor impairment in PD rather than an inability to perform MI (Dominey et al, 1995). Moreover, other studies have found similar performance in PD and control groups when judging hand laterality (Bek et al, 2022;Scarpina et al, 2019;van Nuenen et al, 2012).…”
Section: Introductionmentioning
confidence: 86%